Performance of Invention Toddler Pneumonia Cases in Public Health Centers Municipality Jambi - Rumita Ena Sari; Rizalia Wardiah; Putri Inrian Tari (Poltekkes Kemenkes Palu, 2022)
The prevalence of toddler pneumonia in Jambi was fluktuative since 2019, and never achived of minimal standart services. This study aims to determine performance of finding pneumonia under five by health workers at the Jambi City Health Center in 2021. This type of research was a quantitative study with a Cross Sectional design. The sampling technique used a total sampling of 60 health workers. Data collected by using a questionnaire. The results showed that there was a significant relationship between motivation,, supervision,, support from the head of the health center, training, and support from colleagues, with performance of finding pneumonia. It is hoped that the health center will carry out outreach efforts to the community regarding the prevention of pneumonia which is integrated with the STOP Pneumonia program. It is also hoped that the Jambi City Health Office will routinely hold training on pneumonia under five.